(untitled) (Economic studies journal, 2020)
The main aim of this study was to estimate the impact of oil price fluctuations of oil, non-oil and total trade balance in the Libyan economy in the short and long run, during the period 1988-2018. In order to test for the existence of a long run equilibrium relationship between its variables, the study has utilized Gregory & Hansen (1996) cointegration test. TO analyze the short run dynamics and estimating short run coefficients it has used the Error correction model ECM. furthermore, the study has used cointegration regression approach to estimate the long run coefficients using four estimators "OLS, FMOLS, DOLS. CCR". The main results have indicated a positive correlation between oil and total trade balance and oil price fluctuations, however, a negative correlation between non-oil trade balance and oil price fluctuations. Cointegration test has supported the existence of a long run equilibrium relationship between its variables has been captured. The short and long run coefficients have showed a positive impact of oil price fluctuations on oil and total trade balance, but negative impact on non-oil trade balance.